Investigation of the sequence features controlling aggregation or degradation of prion-like proteins - Cascarina, Sean Micheal, author; Ross, Eric, advisor; Ho, P. Shing, committee member; Di Pietro, Santiago, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2017)
Protein aggregates result from the conversion of soluble proteins to an insoluble form. In some cases, protein aggregates are capable of catalyzing the conversion of their soluble protein counterparts to the insoluble form, resulting in a mode of molecular self-replication. Many of these infectious proteins, or "prions", have been identified and characterized in yeast. This has led to the development of prediction algorithms designed to identify protein domains capable of forming prions. Recently, a number human proteins with aggregation-prone prion-like domains (PrLDs) have been identified, and mutations within PrLDs have been linked to muscular and neurodegenerative disorders. However, the number and diversity of PrLD mutations linked to disease are currently limited. Therefore, the extent to which a broad assortment of PrLD mutations affect intrinsic aggregation propensity, and how well this correlates with aggregation in a cellular context, has not been systematically examined. In Chapter 2, I present evidence suggesting that our prion aggregation prediction algorithm (PAPA) is capable of predicting the effects of a diverse range of mutations on the aggregation propensity of PrLDs in vitro and in yeast. PAPA was also able to predict the effects of many but not all PrLD mutations when the protein was expressed in Drosophila, but with slightly. Therefore, while great strides have been made in predicting intrinsic aggregation propensity, a more complete understanding of the cellular factors that influence aggregation in vivo may lead to further improvement of prion prediction methods. Many intracellular protein quality control factors specialize in recognizing and degrading aggregation-prone proteins. Therefore, prions must evade or outcompete these quality control systems in order to form and propagate in a cellular context. However, the sequence features that promote degradation versus aggregation of prion domains and PrLDs have not been systematically defined. In Chapter 3, I present evidence that aggregation propensity and degradation propensity can be uncoupled in multiple ways. First, we find that only a subset of classically aggregation-promoting amino acids elicit a strong degradation response in PrLDs. Second, the amino acids that promoted degradation of the PrLDs did not induce degradation of a glutamine/asparagine (Q/N)-rich prion domain, and instead led to a dose-dependent increase in the frequency of spontaneous prion formation, suggesting that protein features surrounding aggregation-prone amino acids can modulate their ultimate effects. Furthermore, degradation suppression correlated with Q/N content of the surrounding prion domain, potentially indicating an underappreciated role for these residues in yeast prion domains. The protein features that foster susceptibility or resistance to degradation are further explored in Chapter 4. We find that Q/N-rich domains resist degradation in a primary sequence-independent manner, and can even exert a dominant degradation-inhibiting effect when coupled to a degradation-prone PrLD. Furthermore, susceptibility to degradation was a relatively de-centralized feature of the PrLD, requiring a large portion of the domain surrounding degradation-promoting amino acids to permit efficient protein turnover. Collectively, these results provide key insights into the relationship between intrinsically aggregation-prone protein features and the ability to aggregate in the context of intracellular protein quality control factors.
Keywords: amyloid; prion-like; proteostasis; prion; aggregation; protein degradation